2017
DOI: 10.3892/ol.2017.5772
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating tumor cells in patients with non-small cell lung cancer using a size-based platform

Abstract: Abstract. The detection of circulating tumor cells (CTCs) is limited by the rarity of these cells in the peripheral blood of patients with cancer. Understanding tumor biology may be useful in the development of novel therapeutic strategies for patients with lung cancer. The present study evaluated a novel size-based filtration platform for enriching CTCs from patients with lung cancer. Blood samples were obtained from 82 patients with lung cancer for CTC analysis. CTC enrichment by size-based filtration was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…We observed that a favourable therapy resulted in loose cluster formation while the tight cluster suggested therapy resistance. In addition, these clusters show different phenotypes across 4 cancer types that could be correlated with the number of CTCs reported in each cancer type 20,29,30 . We have enumerated CTCs using pan-CK positive, CD45 negative and DAPI-positive cells in clusters observed on day14 (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that a favourable therapy resulted in loose cluster formation while the tight cluster suggested therapy resistance. In addition, these clusters show different phenotypes across 4 cancer types that could be correlated with the number of CTCs reported in each cancer type 20,29,30 . We have enumerated CTCs using pan-CK positive, CD45 negative and DAPI-positive cells in clusters observed on day14 (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Our results from the present study provide technical feasibility that the EGFR p.T790M mutation can be detected in CTCs using both the OncoBEAM™‐ EGFR or NGS‐56G assay technologies. Soon et al have also shown that the number of CTCs might differ considerably depending on the disease stage; for instance, they found a mean number of 1.48 ± 1.71 CTCs in stage I‐III patients (in 5 mL of total blood) and a mean of 8 ± 9.95 CTCs in stage IV‐V patients using the CellSearch platform . Given the considerable body of existing knowledge clearly indicating that the numbers of CTCs capable of being isolated from a clinical blood sample is likely to be a significant limitation to bringing CTCs into routine use in clinical diagnostics, our findings justify the use of highly sensitive assays such as BEAMing to detect mutations in combinatorial analyses with CTCs (p.T790M assay; 10 tumor cells per 7.5 mL of total blood required to detect EGFR p.T790M following enrichment with ClearCell FX) (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…CTC counting has been proven to be associated with some disease characteristics. Sonn et al [21], described a study with 82 patients with lung cancer, where they found an association of CTC counts with stage disease, as patients with stage IV had more CTCs, compared to stages I-III of TNM system (p = 0,009). Therefore, one of our findings was the correlation of CTC counts with pretreatment status, where we observed that patients with pre-treatment had more CTCs per mL.…”
Section: Discussionmentioning
confidence: 98%